PENGARUH FIRM SIZE, LEVERAGE, FREE CASH FLOW, UKURAN PENAWARAN RELATIF, DAN RATING TERHADAP REAKSI PASAR PADA PENGUMUMAN PENERBITAN SUKUK DAN OBLIGASI KONVENSIONAL PERIODE 2013-2016 - Eva Wulandari; Sugeng Wahyudi (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to investigate factors that influance market reaction on announcement of sukuk and conventional bonds issuance over the period of 2013-2016. Independent variabels that used are firm size, leverage, free cash flow, relative bond size offering, and bond rating. Market reaction is calculated by cumulative abnormal return. This study uses all the announcement of sukuk and conventional bonds issuance during the period 2013-2016 as the population. The final sample are 13 announcements of sukuk issuance and 87 announcements of conventional bonds issuance obtained by purposive method. Cross sectional is used as the type of data in this study. The data of announcements event was obtained through Bloomberg, financial statements from official website of Indonesia Stock Exchange (IDX) and daily stock price from yahoofinance.com then analyzed using t-test, regression and chow test. The analytical tool that used in this study is E-views. The result of this study are leverage, relative bond size offering, and rating significantly have a positive effect to cumulative abnormal return while variabels of firm size and free cash flow have no significant effect to cumulative abnormal return on announcement of sukuk issuance. Then, on the announcement of conventional bonds issuance shows that there are no variables that have a significant effect on CAR. There was an information leak in the announcement of conventional bond issuance marked by a significant market reaction on the day before conventional bonds issuance is announced.